O papel do IFN- na infecção por Leishmania amazonensis - Matheus Batista Heitor Carneiro (2010)
IFN-ã is a key cytokine for protection against many infections caused by a number of intracellular parasites, such as: Leishmania major, Toxoplasma gondii, Trypanosoma cruzi, Plasmodium chabaudi and Mycobacterium tuberculosis. The mechanism by which this cytokine acts is the classical activation of macrophages that expresses iNOS, leading to production of NO, which leads to death of these parasites. The importance of this cytokine in vivo and in vitro is already well established for the models of infection cited. Surprisingly, the same is not true for infection by L. amazonensis. In this case, it was demonstrated that, in vitro, the amastigotes of the parasite are stimulated to proliferate in the presence of IFN-ã. Moreover, the relevance of this cytokine for protection in vivo occurs only in the later times of infection. The mechanism by which IFN-ã is not essential in the initial days of infection is still not understood. Thus, the aim of our study was to investigate the role of IFN-ã during in vivo infection by the strain PH8. Furthermore, the elucidation of the real role of IFN-ã is essential for studies that aim to produce an effective vaccine. Our data confirm the importance of IFN-ã only in the later times of infection, as described for other strains of L. amazonensis. The mechanism by which IFN-ã -/- mice do not exhibit increased susceptibility to infection after 10 weeks appears to be dependent on a balance between expression of arginase I and iNOS, in addition to modulation of IL-10. Despite this limited role at the end of the infection, IFN-ã is essential for immunization by Leishvacin, in a mechanism-dependent of iNOS expression. Our data indicate the importance of this cytokine for the partial control of infection by L. amazonensis, and also for immunization, but suggests the possibility that other factors, still unknown, may be important for infection control in the beginning, and also for the generation of immunity.